Primate Census in Kathmandu and West Parts of Nepal - Chalise, Mukesh Kumar (Journal of Natural History Museum, 2009)
Nepal consists of three major monkey species in different phytoecological zones from Tarai plain to the valleys of high mountains. This paper includes the census data, available for three species of monkeys of Nepal obtained from different research activities. Key words: Census; distribution; Nepal monkey; population Journal of Natural History Museum Vol. 23, 2008 Page 60-64